Reduction of Shipping Cost Volatility in the Global Supply Chain: Consumers and Blockchain - Fadye Saud Alfayad (International Journal of Supply Chain Management, 2020)
Abstract— This report examines the issue of reduction of shipping cost volatility within the global supply chain. The idea is that through the reduction of such supply chain shipping cost volatility, cost savings can be achieved and then passed onto the client firms and from them onto the end-consumer in the commodity chain. This issue is discussed in relation to the way in which blockchain technology can facilitate such cost reductions through the elimination of variance, inventory carrying costs and waste within the supply chain. All of these factors and others such as the integration of smart contracts, space optimization analytics and supply chain volatility indexing among other blockchain supported solutions contribute to shipping cost reduction. Blockchain is described in some depth in order to illustrate its applicability to the supply chain and logistics environment. Blockchain is described as a distributed ledger type system in which all nodes on a given network have full visibility and access to the blocks of date embedded within the system. Furthermore, blockchain is shown to have no centralized management system or authority. The end result is that blockchain is an emerging technology that supports shipping cost reduction at the manufacturing level, distribution level and retail level of any commodity class or product.